1999
DOI: 10.1039/a900277d
|View full text |Cite
|
Sign up to set email alerts
|

An efficient protocol for Sharpless-style racemic dihydroxylation

Abstract: An Efficient Protocol for Sharpless-Style Racemic Dihydroxylation.-Racemic dihydroxylation of various alkenes is efficiently achieved under conditions similar to those of Sharpless asymmetric dihydroxylation using OsCl 3 -quinuclidine as catalytic system and methanesulfonamide as a further additive. Scope and limitation of the reaction are studied, and diastereoselectivity in the dihydroxylation of compounds with stereogenic centers, e.g. (VII) and (IX), is found to be only moderate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…The (E)-iodoalkene 6 was prepared in excellent yield from 1-heptyne by sequential hydroalumination using Dibal-H and halogenation by N-iodosuccinimide 17 ; a subsequent Sonogashira coupling 18 with iodo-ester 5b then gave the (E)-enyne 7. As we clearly did not require homochiral material, this was then bis-hydroxylated regioselectively at the alkene function, as originally reported by the Sharpless group, 19 but using the simpler achiral Warren procedure, 20 which delivered an excellent 86% yield of the required alkyne-diol 8. We were dismayed to find that our initial attempts to carry out a 5-endo-dig iodocyclisation 12 using the alkene-diol 8 met with almost complete failure.…”
Section: Resultsmentioning
confidence: 82%
“…The (E)-iodoalkene 6 was prepared in excellent yield from 1-heptyne by sequential hydroalumination using Dibal-H and halogenation by N-iodosuccinimide 17 ; a subsequent Sonogashira coupling 18 with iodo-ester 5b then gave the (E)-enyne 7. As we clearly did not require homochiral material, this was then bis-hydroxylated regioselectively at the alkene function, as originally reported by the Sharpless group, 19 but using the simpler achiral Warren procedure, 20 which delivered an excellent 86% yield of the required alkyne-diol 8. We were dismayed to find that our initial attempts to carry out a 5-endo-dig iodocyclisation 12 using the alkene-diol 8 met with almost complete failure.…”
Section: Resultsmentioning
confidence: 82%
“…During reaction optimisation studies, it was found that the efficiency of the oxidative cyclisation of 2 to 4 is sensitive to the reagents and reaction conditions; thus, exposure of 2 to other dihydroxylation reaction conditions led to reduced yields of 4 and other products. For example, employing Warrens racemic dihydroxylation reaction conditions [14] gave keto-alcohol 4 in 57 % yield, along with d/l-diol d/l-6 in 15 % yield (Scheme 4). The structure of this diol byproduct was verified by comparison with NMR data obtained for the mixture of meso-and d/l-diol products obtained from the reduction of keto-alcohol 4 (vide infra).…”
Section: Resultsmentioning
confidence: 98%
“…[11] The enynes were obtained in turn from Sonogashira couplings of a 1-alkyne and a 1-bromoalkene, all of which are commercially available. Success in the key cyclisation step (Scheme 5) turned out to be readily achieved using conditions employed previously in our 5-endo-trig cyclisations.…”
Section: Resultsmentioning
confidence: 99%